2000
DOI: 10.1086/308632
|View full text |Cite
|
Sign up to set email alerts
|

General Relativistic Effects on Neutrino‐driven Winds from Young, Hot Neutron Stars andr‐Process Nucleosynthesis

Abstract: Neutrino-driven wind from young hot neutron star, which is formed by supernova explosion, is the most promising candidate site for r-process nucleosynthesis. We study general relativistic effects on this wind in Schwarzschild geometry in order to look for suitable conditions for a successful r-process nucleosynthesis. It is quantitatively discussed that the general relativistic effects play a significant role in increasing entropy and decreasing dynamic time scale of the neutrino-driven wind. Exploring wide pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
363
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(386 citation statements)
references
References 34 publications
20
363
3
Order By: Relevance
“…The production of seed elements in the neutrino-driven wind and the alpha-rich freeze-out scenarios can be enhanced due to the slight increase of the reaction rate at T 9 > 3.5. This may lead to a slightly smaller neutron-to-seed ratio at the onset of r-process, and hence make an appreciable influence on the entropy condition and expansion dynamics of the neutrino-driven wind [4]. Kajino et al have recently studied the sensitivity of the r-process yields to the α(αn, γ) 9 Be reaction rate, and found that a factor of two larger rate would change the final r-process abundances drastically in rapid expansion models of the neutrino-driven wind [45].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of seed elements in the neutrino-driven wind and the alpha-rich freeze-out scenarios can be enhanced due to the slight increase of the reaction rate at T 9 > 3.5. This may lead to a slightly smaller neutron-to-seed ratio at the onset of r-process, and hence make an appreciable influence on the entropy condition and expansion dynamics of the neutrino-driven wind [4]. Kajino et al have recently studied the sensitivity of the r-process yields to the α(αn, γ) 9 Be reaction rate, and found that a factor of two larger rate would change the final r-process abundances drastically in rapid expansion models of the neutrino-driven wind [45].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In this rapid expansion, there is essentially no time for the triple alpha reaction to set in and, instead, the ααn reaction becomes again crucial for the r-process. The necessary expansion time is determined in comparison with the reaction time scale of the ααn reaction [4]. A more recent study reveals that the reaction flow can go through the neutron-rich region of light elements in the rapidly expanding wind [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Shown by white dots in Fig. 1 are the isotopes included in our reaction network [7,9]. Let us remind the readers that there were at least three difficulties in the previous theoretical studies of the r-process.…”
Section: R-process and The Key Reactionmentioning
confidence: 99%
“…Highlight abundance scales to logY , where Y is the number fraction of each nucleus. White dots show the nuclei included in the reaction network code [7,9]. The neutrino-driven wind model used is for L ν = 10 52 ergs/s and M = 2M ⊙ [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation